2019
DOI: 10.3390/ma12223691
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Copper Alloying in a TNTZ-Cux Alloy

Abstract: Alloying copper into pure titanium has recently allowed the development of antibacterial alloys. The alloying of biocompatible elements (Nb, Ta and Zr) into pure titanium has also achieved higher strengths for a new alloy of Ti-1.6 wt.% Nb-10 wt.% Ta-1.7 wt.% Zr (TNTZ), where strength was closer to Ti-6Al-4V and higher than grade 4 titanium. In the present study, as a first step towards development of a novel antibacterial material with higher strength, the existing TNTZ was alloyed with copper to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They come up with a decision that the low elastic modulus associated with the new modified alloy allows it to be practiced in dental and orthopedic implants. Fowler et al 62 added sterile Cu in the alloy of Ti-Nb-Ta-Zr and studied the concentration of Cu on the hardness of the mentioned alloy. They concluded that the hardness of said Ti-alloy is proportional to the percentage of Cu addition.…”
Section: Classification and Properties Of Ti-alloysmentioning
confidence: 99%
“…They come up with a decision that the low elastic modulus associated with the new modified alloy allows it to be practiced in dental and orthopedic implants. Fowler et al 62 added sterile Cu in the alloy of Ti-Nb-Ta-Zr and studied the concentration of Cu on the hardness of the mentioned alloy. They concluded that the hardness of said Ti-alloy is proportional to the percentage of Cu addition.…”
Section: Classification and Properties Of Ti-alloysmentioning
confidence: 99%
“…Lee et al claimed that the Ti-Nb-Ta-Zr (TNTZ) system showed promising properties for biocompatibility and strength comparable to those of Ti-6Al-4V. The alloys in the range of 3-10 wt% Cu all had Ti 2 Cu, which may cause the potential antibacterial ability of the material (Fowler et al, 2019a). Shi et al developed a new titanium alloy, Ti-13Nb-13Zr-5Cu (TNZ-5Cu), with a low elastic modulus and good antibacterial properties.…”
Section: Ti-zr-cu Alloysmentioning
confidence: 99%
“…The article shows combination of different processing routes (hot-rolling, annealing and solution treatment) for design of alloys of different mechanical properties (hardness and Young's modulus). Fowler et al [4] modified Ti-Nb-Ta-Zr alloy by addition of antibacterial Cu. As the effect of microstructural changes, the few % of Cu addition results in significant increase of alloys hardness.…”
mentioning
confidence: 99%